Integrated Visitor Management System with Smart Hand Sanitizer based on IoT Approach - Hafidz, Adli Al; Pujiharsono, Herryawan; Kadarisman, Kadarisman; Yusro, Muhammad (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
Establishing visitor management system is necessary to manage the total number of visitors especially in pandemic when the protocol of social distancing is applied. The purpose of this research is to design a visitor management system integrated with an automatic Internet of Things (IoT)-based hand sanitizer using Arduino. This research contributes to answering the two challenges which are managing the total number of visitors and providing protection against bacteria or viruses. The improvement of this system compared to the existing similar approach is the automatic hand sanitizers could be installed at two entrances and exits which can simultaneously limit the number of visitors who will be monitored through the IoT platform. This system is designed with Arduino Uno R3 components as a microcontroller, ultrasonic sensors which will be installed at two entrances and exits, and automatic hand sanitizer using a water pump. For remote monitoring use the IoT platform with the ESP8266 ESP-01 Wi-Fi module as a link. From the results of testing this system, the results of testing the correct hand distance when using a hand sanitizer are from 3 cm to 9 cm and the right amount of hand sanitizer liquid volume is approximately 1 ml for a duration of 250 milliseconds. The system design has been successful for visitor management and the hand sanitizer works well. The Thingspeak webserver can receive visitor data and send it to the MIT app as a display for remote monitoring. Hopefully, this system could support the situation which needs to manage the restriction of total number visitors and hygiene practice in a more efficient way.